Factors associated with experienced discrimination among people using mental health services in England. (3rd July 2016) - Hamilton, S.; Corker, E.; Weeks, C.; Williams, P.; Henderson, C.; Pinfold, V.; Rose, D.; Thornicroft, G.
Abstract: Background : Research has found considerable variation in how far individuals with a diagnosis of mental illness experience discrimination. Aims : This study tested four hypotheses: (i) a diagnosis of schizophrenia will be associated with more discrimination than depression, anxiety or bipolar disorder; (ii) people with a history of involuntary treatment will report more discrimination than people without; (iii) higher levels of avoidance behaviour due to anticipated discrimination will be associated with higher levels of discrimination and (iv) longer time in contact with services will be associated with higher levels of discrimination. Method : Three thousand five hundred and seventy-nine people using mental health services in England took part in structured telephone interviews about discrimination experiences. Results : A multiple regression model found that study year, age, employment status, length of time in mental health services, disagreeing with the diagnosis, anticipating discrimination in personal relationships and feeling the need to conceal a diagnosis from others were significantly associated with higher levels of experienced discrimination. Conclusion : Findings suggest that discrimination is not related to specific diagnoses but rather is associated with mental health problems generally. An association between unemployment and discrimination may indicate that employment protects against experiences of discrimination, supporting efforts to improve access to employment among people with a diagnosis of mental illness.